3D numerical investigations of the effect of fill factor on dispersive and distributive mixing of rubber under non‐isothermal conditions. Issue 3 (10th November 2018) - Ahmed, Istiaque; Chandy, Abhilash J.
Abstract : Three‐dimensional, non‐isothermal, transient computational fluid dynamics simulations are conducted for rubber mixing with a set of two‐wing rotors in a partially filled chamber. The main objective is to analyze the effect of different fill factors of rubber on dispersive and distributive mixing characteristics by simulating 15 revolutions of the rotors rotating at 20 rpm. 60%, 70%, 75%, and 80% are the four different fill factors chosen for the study. An Eulerian multiphase model is employed to simulate two different phases, rubber and air, and the volume of fluid technique is used to calculate the free surface between two phases, in addition to the continuity, momentum and Energy equations. To characterize non‐Newtonian, highly viscous rubber, shear rate and temperature dependent Carreau‐Yasuda model has been used. A set of more than 3, 600 massless particles are injected after a certain period of time to calculate several quantities in terms of dispersive and distributive mixing. Both the Eulerian and Lagrangian results showed that, fill factors between 70% and 80% presented the most reasonable and efficient mixing scenario, thus exhibiting the best dispersive and distributive mixing characteristics combined. POLYM. ENG. SCI., 59:535–546, 2019. © 2018 Society of Plastics Engineers